2016
DOI: 10.1111/1462-2920.13579
|View full text |Cite
|
Sign up to set email alerts
|

Growth phase‐dependent control of R27 conjugation is mediated by the interplay between the plasmid‐encoded regulatory circuit TrhR/TrhY‐HtdA and the cAMP regulon

Abstract: Plasmids of the incompatibility group HI1 (IncHI1) have been isolated from several Gram-negative pathogens and are associated with the spread of multidrug resistance. Their conjugation is tightly regulated and it is inhibited at temperatures higher than 30°C, indicating that conjugation occurs outside warm-blooded hosts. Using R27, the prototype of IncHI1 plasmids, we report that plasmid transfer efficiency in E. coli strongly depends on the physiological state of the donor cells. Conjugation frequency is high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 41 publications
2
15
1
Order By: Relevance
“…Surprisingly, 5 mM cAMP added throughout the growth did not significantly change the conjugation efficiency in Δcya background and did not restore the growth‐dependent regulation (Figure S2). Such observation disagrees with some prior studies showed that Δcya ‐dependent regulation deficiency in mating of IncF pRK100 and IncH R27 plasmids was overcome by adding extracellular cAMP . Nevertheless, a nonmonotonic response of F‐conjugation to cAMP was recorded before and may reflect a complex nature of the cAMP regulation …”
Section: Resultscontrasting
confidence: 91%
See 3 more Smart Citations
“…Surprisingly, 5 mM cAMP added throughout the growth did not significantly change the conjugation efficiency in Δcya background and did not restore the growth‐dependent regulation (Figure S2). Such observation disagrees with some prior studies showed that Δcya ‐dependent regulation deficiency in mating of IncF pRK100 and IncH R27 plasmids was overcome by adding extracellular cAMP . Nevertheless, a nonmonotonic response of F‐conjugation to cAMP was recorded before and may reflect a complex nature of the cAMP regulation …”
Section: Resultscontrasting
confidence: 91%
“…We found that the transcripts for the essential transfer components were elevated in the stationary state donor cells (Figure a). Similar observations correlating mRNA levels for essential components and conjugation efficiency were previously reported for prototypic F plasmids and R27 IncH system . Therefore, we concluded that levels of the transfer proteins indeed correlate with the observed levels of the transcripts for the growth‐dependent conjugative systems.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Its complete nucleotide sequence is available, and the replication and conjugation determinants are well characterized (Taylor et al, ; Couturier et al, ; Maher et al, ; Gabant et al, ; Newnham and Taylor, ; Sherburne et al, ; Lawley et al, , ; Alonso et al, ). The interplay between the R27 plasmid and the bacterial chromosome has been studied, and functional interactions between regulators from both genetic elements have been characterized (Doyle et al, ; Baños et al, ; Dillon and Dorman, ; Gibert et al, , ). Moreover, the impact of the presence of R27 on the global expression profile of Salmonella under some environmental conditions has been described (Paytubi et al, ).…”
Section: Introductionmentioning
confidence: 99%